Tradisi Balimau Kasai di Tanah Melayu Riau dalam Perspektif Fenomenologi Edmund Husserl - Putri Rizca Mardeni; Jimmi Copriady (Jurnal Filsafat Indonesia, 2023)
This paper aims to see the meaning of the Balimau Kasai tradition in Riau Malay Land in the perspective of Edmund Husserl's phenomenology, namely through self-awareness gained from every experience. The Balimau Kasai tradition can be interpreted as a tradition of the Riau Malay community to purify themselves, gratitude and joy in welcoming the holy month of Ramadan. The influence of the times has made the tradition interpreted differently by today's children. They interpret this tradition as one of their own pleasures that can fade the positive values ​​of the Balimau Kasai tradition.